2015
DOI: 10.1002/mnfr.201500336
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of polyunsaturated fat improves the saturated fatty acid‐mediated impairment of HDL antioxidant potential

Abstract: SFA intake impairs the antioxidant potential of HDL and increases serum levels of oxidized lipoprotein species whereas the antioxidant potential of HDL is enhanced after PUFA consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Oxidation kinetics were followed by continuous monitoring of the formation of conjugated dienes50. After 2.5 μM CuSO 4 was added to the lipoproteins, continuous monitoring was performed at 234 nm absorbance (BioTek Synergy, Winooski, VT) at 37 °C for 4 h, using a 96-microwell plate for UV detection (Greiner, Hannover, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation kinetics were followed by continuous monitoring of the formation of conjugated dienes50. After 2.5 μM CuSO 4 was added to the lipoproteins, continuous monitoring was performed at 234 nm absorbance (BioTek Synergy, Winooski, VT) at 37 °C for 4 h, using a 96-microwell plate for UV detection (Greiner, Hannover, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…After 2.5 μM CuSO 4 was added to the lipoproteins, continuous monitoring was performed at 234 nm absorbance (BioTek Synergy, Winooski, VT) at 37 °C for 4 h, using a 96-microwell plate for UV detection (Greiner, Hannover, Germany). The lag phase was calculated as described previously50. The kinetics of LDL in LDL+HDL incubations was calculated by subtracting the kinetics of HDL incubated without LDL from the total kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the biggest difference between marine lipids and terrestrial lipids is that marine lipids are rich in polyunsaturated fatty acids (PUFA) especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) (Cedó et al 2015). Accumulating evidence has shown that marine lipids exhibit significant efficacy in preventing hyperlipidemia, nonalcoholic fatty acid, diabetes, cancers, inflammatory, and neurodegenerative diseases.…”
Section: Lipidsmentioning
confidence: 99%
“…Total RNA from liver and small intestine was extracted using TRIzol LS Reagent (Invitrogen, Carlsbad, CA) following the manufacturer's instructions, and purified using the RNeasy Plus Mini Kit (Qiagen, Hilden, Germany). cDNA was generated using Oligo(dT) 23 and dNTPs mix (Sigma-Aldrich) and M-MLV Reverse Transcriptase RNase H Minus Point Mutant (Promega, Madison, WI), and was subjected to quantitative real-time PCR amplification using the TaqMan Master Mix (Applied Biosystems, Foster City, CA) and specific TaqMan probes (Applied Biosystems) for abca1 (Mm004426464_m1), abcg5 (Mm00446241_m1), abcg8 (Mm00445970_m1), acaca (Mm01304257_m1), cyp7a1 (Mm00470430_m1), fasn (Mm01253292_m1), npc1l1 (Mm01191972_m1), nr1h3 (Mm00443451_m1), and gapdh (Mm99999915_g1) as the internal control gene. Reactions were run on a CFX96TM Real-Time System (Bio-Rad, Hercules, CA) according to the manufacturer's instructions.…”
Section: Quantitative Real-time Pcr Analysesmentioning
confidence: 99%